Characterization of infectious laryngotracheitis virus isolated from commercial layer chickens in Bangladesh during the year 2021–2022 - Kamal, Md Mostofa; Sadekuzzaman, Mohammad; Parvin, Kohinoor; Haque, Md Enamul; Hayat, Sajedul; Islam, Md Ariful; Khatun, Mst Minara; Siddique, Mahbubul Pratik; Nahar, Sham Soun; Khasruzzaman, A K M; et al. (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Infectious laryngotracheitis virus (ILTV) is responsible for causing infectious laryngotracheitis (ILT), which is a rapidly spreading and extremely transmissible disease in chickens. The current research aims to isolate and characterize ILTV from layer chickens in Bangladesh. Materials and Methods: A total of 345 samples (trachea, larynx, and lungs) were collected from ILT-suspected dead and sick layer chickens of 32 ILT-suspected farms in three different outbreak districts (Gazipur, Tangail, and Mymensingh) of Bangladesh during the outbreak year 2021-2022. Rapid detection kits examined the samples for avian influenza virus (AIV) and Newcastle disease virus (NDV). ILTV-specific primers were used to screen 72 NDV- and AIV-negative samples by polymerase chain reaction (PCR). Using chorioallantoic membrane (CAM), the study isolated the ILT virus from 9 to 10-day-old seronegative embryonated chicken eggs (ECEs) using selected PCR-positive samples. The virus was confirmed using nucleotide sequencing, agar gel immunodiffusion test (AGIDT), viral neutralization test (VNT), and pathogenicity evaluations using mortality index for chicken embryos (MICEs) and intra-tracheal pathogenicity index (ITPI). Results: The results indicated that among the PCR-positive 10 samples, only two (Alim_ILT_1001 and Alim_ILT_1,000) were found positive using ECEs. There were two field isolates of ILTVs, as shown by the amplicon size of the ICP4 gene-based PCR. A phylogenetic study of the ICP4 gene revealed that the recent isolates have a close similarity with the ILTV isolates of Turkey, Bangladesh, and Australia. AGIDT revealed strong precipitation lines due to ILTV-specific antibodies reacting with field viruses, while VNT neutralized both isolates with conventional ILTV antibodies. The pathogenicity testing indicated that Alim_ILT_1001 had MICE and ITPI values of 0.77 and 0.63, whereas Alim_ILT_1,000 had 0.71 and 0.57. Conclusion: Both the ILTV isolates have similarities with the isolates of Turkey, Bangladesh, and Australia, and they are highly virulent for chickens. Adv. Vet. Anim. Res., 11(2): 398-407, June 2024 http://doi.org/10.5455/javar.2024.k789